(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article outlines the laws governing the development of a teacher’s personality in the analysis of innovative activities. The author also reflected on the psychological map of the individual, his characteristics, and research in the field of acmeology to this day.